Influence of Aggression Management Program in Reducing Aggressive Behavior of Filipino Children in Conflict with the Law - Consuelo Oliveros Peralta; Jemerson Naceno Dominguez (Universitas Katolik Soegijapranata, 2020)
Aggression is a behavior that intent to hurt others. Despite collective researches about aggression, there is a dearth in fully established psychosocial programs for the Children in Conflict with the Law (CICL) and evaluating program directed to aggressive behavior in the Philippines. Eight CICL housed in an institution under the supervision of the DSWD-Dasmariñas were the primary source of data. The study seeks to describe the pre-and-post mean scores of aggressions and determine the significant difference in aggression reduction before and after exposure to AMP. Employing the quasi-experimental design, the researchers administered the intervention and conducted repeated-measures to measure the effectiveness of AMP thru combined approaches of CBT-EFT in reducing their aggression level. Findings revealed that their aggression in the areas of physically aggressive responses, and verbally aggressive reactions were diminished after participating in the AMP, with the inclusion of counseling sessions in addressing problematic concerns related to aggressive behavior.